2008
DOI: 10.1002/rmv.569
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B virus and hepatitis C virus infections

Abstract: Occult HBV infection is a well-recognised clinical entity characterised by the detection of HBV-DNA in serum and/or in liver in the absence of detectable hepatitis B surface antigen (HBsAg). Occult HBV infection has been described not only in patients who have resolved an acute or chronic HBV infection but also in patients without any serological markers of a past HBV infection. Occult HBV infection in patients with chronic HCV infection may induce more severe liver disease and lower response rate to interfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 147 publications
1
39
0
4
Order By: Relevance
“…Non B, non C hepatitis is an important cause of post-transfusion hepatitis which can remain silent for many years and present as cryptogenic cirrhosis. [31][32][33] Clinicopathological correlation has shown that NASH and autoimmune hepatitis are leading causes of cryptogenic cirrhosis. [34][35][36][37] Though asymptomatic autoimmune hepatitis is not known, previously unrecognized cirrhosis has been described, especially in patients with acute presentation of autoimmune hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Non B, non C hepatitis is an important cause of post-transfusion hepatitis which can remain silent for many years and present as cryptogenic cirrhosis. [31][32][33] Clinicopathological correlation has shown that NASH and autoimmune hepatitis are leading causes of cryptogenic cirrhosis. [34][35][36][37] Though asymptomatic autoimmune hepatitis is not known, previously unrecognized cirrhosis has been described, especially in patients with acute presentation of autoimmune hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…The virus is not detectable with conventional testing but can be found with ultra-sensitive tests [78,79].The virus can be detected by antibody test for virus core protein and the viral genome [80].It may be found in people with antihepatitis C-antibodies but with normal levels of liver enzymes ‗in antibody-negative people with ongoing elevated liver enzymes of unknown cause, in healthy populations without evidence of liver disease, and groups at risk for HCV infection including those on hemodialysis or family members of people with occult HCV.The clinical relevance of this form of infection is under investigation [81].The rate of occult infection in those apparently cured is controversial but appears to be low [66].…”
Section: Hcv Negative or Occult Infectionmentioning
confidence: 99%
“…Gelişmiş tarama prosedürlerine rağmen anti-HCV antikorları saptanamayan hemodiyaliz hastalarında yeni tarama stratejilerinin geliştirilmesi gerekliliği açıktır. HCV infeksiyonunun patogenezini araştıran çalışmalar HCV'nin ekstrahepatik alanda replike olduğunu ve gizli infeksiyon yaptığını kanıtlamıştır (10,11,23). Özellikle HCV infeksiyonu açısından yüksek risk altındaki hemodiyaliz hastalarında yapılacak olan kapsamlı araştırmalar, bu hasta grubunda gerçek HCV infeksiyonu prevalansının saptanmasına olanak sağlayacağı gibi moleküler testlerin rutin kullanıma girmesi, diyaliz makinelerinin ortak kullanımı konusundaki tartışmalara yol gösterecek ve tedavi indikasyonlarının net olarak belirlenmesine olanak sağlayacaktır.…”
Section: İrdelemeunclassified
“…Bulaşma sonrası spontan olarak iyileşen, ancak anti-HCV pozitifliği devam eden hemodiyaliz hastaları HCV infeksiyonu olanlara ayrılmış diyaliz makinelerinde diyalize alınırlarsa reinfeksiyon riskine sahip olurlar. Periferik kandaki mononükleer hücrelerde (PKMNH) viral RNA replikasyonu devam eden gizli ("occult") HCV infeksiyonu olan hastalar transfüzyon veya hemodiyaliz uygulamaları sırasında virusun yayılması açısından potansiyel risk oluştururlar (10,11).…”
Section: Introductionunclassified